Plan the Generation of the Al Qur’an Memorizers Since 1000 First Day of Life; Study Based on Al Qur’an and Nutrition Science - Muhammad Ridho Nugroho (CV Media Inti Teknologi, 2023)
The critical period for the formation of the fetal brain is from the 8th day to the end of the 7th week of pregnancy. The formation of a child's brain cells begins in the first 1,000 days of life. To produce children who memorize the Qur'an, preparations must be made from this phase. The method of writing this article uses literature study, namely studying various literature that discusses how to produce generations of memorizers of the Qur'an from an early age starting from the beginning of a mother's pregnancy which is studied from the perspective of nutritional factors and child intelligence and refers to verses in the Al-Qur'an 'an. The results of the research there are several things that must be done, namely ensuring a balanced nutritional intake during pregnancy and consumption of vitamins. Gynecological examination to the midwife or obstetrician at least 4 times during pregnancy. Exclusive breastfeeding is given for 6 months, breastfeeding until the age of 2 years which is supplemented with complementary foods (MP-ASI). Nutritious food in sufficient quantities can maintain milk production and the baby grows healthy. Weigh babies routinely every month at Posyandu and basic immunization is mandatory. Good education and teaching the Qur'an to children from an early age. The pattern of parenting and stimulation of children is in accordance with their growth and development. Regulating the spacing of pregnancies and maintaining sanitation and hygiene so as not to get infected and diarrheal diseases.